2018
DOI: 10.1080/15384101.2018.1534511
|View full text |Cite
|
Sign up to set email alerts
|

EXO1 overexpression is associated with poor prognosis of hepatocellular carcinoma patients

Abstract: The roles of exonuclease 1 (EXO1) in hepatocellular carcinoma (HCC) tumorigenesis and progression remain unclear. This study aimed to assess the prognostic value and therapeutic potential of EXO1 in HCC. Exo1 gene copy numbers were obtained from three Oncomine microarray datasets (n = 447). EXO1 mRNA expression was validated by semi-quantitative PCR and QuantiGene® 2.0 assays. Cell growth curve and colony formation were performed to asses the cell proliferation. Clonogenic assay, flow cytometry, and immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Also, due to its role in DNA replication repair and homology-directed repair, the relationships of EXO1 and BRCA1/2 mutations and its underlying mechanism have become an important focus to be studied (Lemacon et al, 2017). A recent study found that the EXO1 expression level was elevated in hepatocellular carcinoma patients and its overexpression was correlated with larger tumor size, increased lymph node metastasis, and thus proving its potential therapeutic value for hepatocellular carcinoma as a promising prognostic marker (Dai et al, 2018). Our findings were validated by another study to some extent, and they found DEPDC1, EXO1, RRM2 and some proteins had enhanced expression in the ductal carcinoma in situ and invasive ductal carcinoma (Kretschmer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Also, due to its role in DNA replication repair and homology-directed repair, the relationships of EXO1 and BRCA1/2 mutations and its underlying mechanism have become an important focus to be studied (Lemacon et al, 2017). A recent study found that the EXO1 expression level was elevated in hepatocellular carcinoma patients and its overexpression was correlated with larger tumor size, increased lymph node metastasis, and thus proving its potential therapeutic value for hepatocellular carcinoma as a promising prognostic marker (Dai et al, 2018). Our findings were validated by another study to some extent, and they found DEPDC1, EXO1, RRM2 and some proteins had enhanced expression in the ductal carcinoma in situ and invasive ductal carcinoma (Kretschmer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…EXO1 has been associated with different types of cancers owning to its mutations, including colon, breast, ovarian, lung, pancreatic, and gastric tract cancer (Bau et al, ; Hansen et al, ; Jin et al, ; Sun, Zheng, & Shen, ). Nevertheless, the overexpression of EXO1 has also been reported in several other cancers associated with poor prognosis, which in part is related to increased DNA repair activity (Axelsen, Lotem, Sachs, & Domany, ; Dai et al, ; de Sousa et al, ; Muthuswami et al, ). In this study, AURKA, CCNB1, CCNF, and EXO1 were significantly upregulated in CRC compared with normal samples, and in CRC patients, the survival rate was positively correlated with the high expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN3 has been correlated with poor tumor differentiation and advanced tumor stage by promoting cell proliferation in HCC (37). HOXD9 acts as a tumor promoter to drive metastasis by regulating ZEB1 in HCC (38), and EXO1 overexpression is associated with poor prognosis in HCC patients (39); however, there have been few reports regarding the effect of NEIL3 on HCC. Two selected genes show different trends in comparison with TCGA data, likely due to race and sample size, which needs further con rmation using larger datasets.…”
Section: Discussionmentioning
confidence: 99%